Autonomy and human rights in a kantian perspective - Cortés Rodas, Francisco (Estudios de Filosofía, 1994)
In the course of present discussion on moral universalism a thesis has developed regarding the necessary separation between morality and politics. The problem contained in this thesis, that is to say, the independence of politics with respect to morality, is rooted in the positivization of the former. In order to elude a negative consequence such as this it is necessary to look for the complimentary character of the two spheres. This article aims at pointing out a possible way to construct such character by means of the reconstruction of certain elements in Kant's and Rawls' ethical reasoning.